Higher Education in Germany-Recent Developments in an International Perspective - Hüther, Otto (Higher Education Dynamics,, 2018)
Otto Hüther and Georg Krücken analyze the developments of the last 20 years in their new book on German higher education. The foreign observer of German higher education, even the informed foreign observer, struggles to find denominators, not to mention common denominators of a bewildering array of approaches. Otto Hüther and Georg Krücken, in this book, do an absolutely splendid job of offering theoretical perspectives, qualitative and quantitative data, and comparative assessments This book discusses the main higher education structures in Germany, both conceptually and with a particular emphasis on recent developments like, e.g., the growth and differentiation of the system, governance reforms, and the Excellence Initiative. It analyses recent developments from an international perspective, as the German system is clearly embedded in broader, transnational trends. As such, the book provides a comprehensive and detailed account of both new dynamics and stable paths in the German higher education system. This book will be of interest to scholars and students dealing with higher education or Germany as an object of study (e.g. in education research, science studies, organization studies, sociology, psychology, political science), and to higher education managers, leaders, and policymakers who are interested in recent trends in German higher education.